Small, medium and micro enterprise promotion in the Western Cape clothing industry : the way forward for SMME's promotion in South Africa - Matshedisho, Knowledge Rajohane (Department of Sociology, 2014)
The object of this dissertation is to describe the extent to which the government has assisted small, medium and micro enterprises (SMME's) in the Western Cape clothing industry. The ultimate aim is to propose a way forward in the light of what the government has done so far in terms of SMME's promotion since 1994 and the recent economic and social developments in South Africa and abroad. The study is targeted at SMME's that are owned by previously disadvantaged communities in the Western Cape metropolitan area. It does not focus on well-established SMME's. The government's SMME's promotion strategy emphasises the need to economically empower previously disadvantaged communities through measures such as SMME's promotion in those communities. It is for this reason that I chose to research this category of SMME's. The observation of this dissertation is that the government has been successful in coming up with the strategy for SMME's promotion and setting up structures for implementation in order to overcome barriers to the growth of SMME's in South Africa. However, there is still work to be done towards the success of these SMME's with primary responsibility falling on local business service centres as grassroots organisations. Bibliography: leaves 168-178.